Prevalencia de la asociación entre la depresión y algunos componentes del síndrome metabólico en Tarerio, Mich. - Mendoza Amaro, Alejandro (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
Depression (WHO, 2001) and metabolic syndrome (WHO, 2000, IDF, 2006) are global public health problems; Epidemiological studies in urban prevalence of the metabolic syndrome 10.2% in the adult population (Del Rio et al, 2005) is observed. In Mexico, along the prevalence of depression and dysthymia life is 5.7% (Medina M, 2003), the approximate numbers found in industrialized countries. Recent studies have detected throughout the world, an association between these two conditions (Vogelzangs N, 2009; McIntyre R, 2009; Vanhala M, 2009; Richter N, 2009; Takeuchi T, 2009). In Mexico has also documented this association (López S, Alveano Carranza J and J, 2008). General Objective: To estimate the prevalence of the association between depression and three components of metabolic syndrome (central obesity, hypertension and diabetes mellitus type 2) in a rural community Purépecha. Specific: To estimate the prevalence of depression and three components of metabolic syndrome in the community. Design: Cross-sectional, analytical and observational study. The sample is a convenience sample. Selection of the universe and the sample Tarerio community, municipality of Tzintzuntzan, Michoacan was chosen.

La depresión (OMS, 2001) y el síndrome metabólico (OMS, 2000, IDF, 2006) son problemas de salud pública mundial; en los estudios epidemiológicos urbanos se observa una prevalencia del síndrome metabólico del 10.2% en la población adulta (Del Río y cols, 2005). En México, la prevalencia a lo largo de la vida de depresión y distimia es del 5.7% (Medina M, 2003), cifras aproximadas a las encontradas en países industrializados. Estudios recientes han detectado a lo largo del mundo, una asociación entre estos dos padecimientos (Vogelzangs N, 2009; McIntyre R, 2009; Vanhala M, 2009; Richter N, 2009; Takeuchi T, 2009). En México también se ha documentado esta asociación (López S, Alveano J y Carranza J, 2008). Objetivo general: Calcular la prevalencia de la asociación entre depresión y tres componentes del síndrome metabólico (obesidad central, hipertensión arterial sistémica y diabetes mellitus tipo 2) en una comunidad rural Purépecha. Específico: Estimar la prevalencia de depresión y tres componentes del síndrome metabólico en la comunidad. Diseño: Estudio transversal, analítico y observacional. La muestra es una muestra conveniente. Selección del universo y la muestra: Se escogió la comunidad de Tarerio, municipio de Tzitzuntzán, Mich.
Facultad de Ciencias Médicas y Biológicas. Maestría en Ciencias de la Salud
Keywords: info:eu-repo/classification/cti/3; FCMB-M-2011-0047; Depresión; Síndrome metabólico; Prevalencia; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2920